Behavioral anomalies and energy-related individual choices: The role of status-quo bias - Julia Blasch; Claudio Daminato (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
The literature on the energy-efficiency gap discusses the status-quo bias as a behavioral anomaly that potentially increases the energy consumption of a household through at least three channels: (1) by making consumers keep their energy-using durables as long as possible, until wearout forces them to replace their equipment (2) by making consumers choose new energy-using durables that resemble the existent ones that need replacement, and (3) by making consumers overuse appliances in an attempt to mentally amortize the initial investment cost. The results presented in this study are an attempt to empirically investigate the extent to which the presence of a bias towards the status quo is linked to residential electricity consumption through two out of the above mentioned three channels: non-replacement of old appliances and overuse of appliances. Using data from a large household survey conducted in three European countries, we find that our measure of status-quo bias is a significant predictor of both the age of home appliances as well as the level of consumption of energy services of a household. The tendency of status-quo biased individuals to keep their appliances longer and to use them more intensely is also reflected in the total electricity consumption of their households, which is found to be around 5.7% higher than for households of non-biased individuals. This research thus provides some first empirical evidence that the status-quo bias has the potential to create a substantial barrier to increasing residential energy efficiency. Our findings prompt policy makers to design instruments that take this barrier into account.
Keywords: D12; D91; Q41; Q50; 330; status-quo bias; loss aversion; appliances replacement; residential energy consumption; energy-related financial literacy